El liderazgo y la productividad del personal administrativo de la unidad de gestión educativa local Sánchez Carrión Huamachuco 2019 - Mauricio Cruz, Celenia Karol (2020)
This research work was proposed with the purpose of establishing the relationship between leadership and productivity of the administrative staff of the Sánchez Carrión Huamachuco Local Educational Management unit as of 2019.The methodology used for the present work was descriptive transversal correlational, quantitative approach. The population was a total of 150 workers, from which a sample of 107 workers from the Sánchez Carrión Huamachuco Local Educational Management Unit was obtained as of 2019. The instruments used to measure the variable were questionnaires. The first questionnaire used was the Multifactorial Leadership Questionnaire (MLQ), developed by Bernard Bass and Bruce Avolio (2000), which was adapted to the reality of the Institution; it consists of 41 questions on a Likert scale and served to measure the first variable. The second questionnaire, in charge of measuring the second variable, consists of 15 questions rated on a Likert scale. The results of the research showed a significant relationship, since, after the application of Spearman's RHO statistical technique, a significance level of 0.000 was obtained, less than 0.05. Furthermore, the correlation coefficient ("r") was 0.713, indicating a considerable positive relationship. As a conclusion, the research hypothesis was accepted, stating that there is a relationship between leadership and productivity of the administrative staff of the Sánchez Carrión Huamachuco Local Educational Management unit as of 2019.